Investigation of Coulomb logarithm and relaxation processes in dense plasma on the basis of effective potentials - Kodanova, S.K.; Ramazanov Т.S.; Hoffmann, D.H.H.; Issanova, M.K.; Moldabekov, Zh.A. (Recent Contributions to Physics, 2014)
In this paper the relaxation properties of non-isothermal dense plasmas were studied. The dense plasma is considered for which quantum effects must be taken into account at short distances. Based on the effective interaction potentials between particles, the Coulomb logarithm for two-temperature non-isothermal dense plasmas was obtained. To obtain the Coulomb logarithm the scattering angle was calculated in binary collision approximation. These potentials take into consideration long-range multi-particle screening effects and short-range quantum-mechanical effects in two-temperature plasmas. The relaxation processes in such plasmas were studied using the Coulomb logarithm. The relaxation times of the temperature in the plasma were calculated for different density values on the basis of the Coulomb logarithm using the effective potential. The obtained results were compared with theoretical works of other authors and with the results of molecular dynamics simulation.